Anakinra reduces lung inflammation in experimental acute lung injury. Issue 2 (9th December 2021) - Engeroff, Paul; Belbézier, Aude; Monsel, Antoine; Klatzmann, David
Abstract: Introduction: Acute respiratory distress syndrome (ARDS) is a severe form of acute lung injury (ALI) resulting in life‐threatening hypoxaemia. Although ARDS can be caused by a variety of pathogens or major trauma, it is best known as the major cause of mortality in COVID‐19 patients. Since ARDS is often associated with dysregulated inflammatory immune responses, immunomodulatory approaches represent a possible treatment option. The objective of this study was to evaluate the therapeutic potential of interleukin (IL)‐1 blockade using Anakinra in a mouse model of lipopolysaccharide (LPS)‐induced ALI. Methods: We evaluated the effects of a daily subcutaneous Anakinra treatment in a mouse model of LPS‐induced ALI. We monitored body weight to assess the general health status of the mice. Two days after ALI induction, we evaluated the inflammatory cytokine MIP‐2 as well as protein levels in bronchoalveolar lavage (BAL) fluids. Two and nine days after ALI induction, we evaluated infiltrating leukocytes in BAL fluid and lung tissue. Results: Anakinra treatment reduced ALI‐induced weight loss compared to nontreated groups. At Day 2, Anakinra treatment reduced levels of MIP‐2 and protein in BAL fluids and reduced frequencies of NK cells and neutrophils in the lung tissue. Nine days after ALI induction, Anakinra treated mice displayed reduced levels of neutrophils and alveolar macrophages in BAL fluids. Conclusions: IL‐1 blockade using Anakinra reduced classical hallmarks of inflammation in a mouse model of ALI. Our data support ongoing and future research on the evaluation of Anakinra as a potential treatment option in ARDS. Graphical abstract: Acute respiratory distress syndrome (ARDS) is a severe lung disease currently lacking specific therapeutics. We show that interleukin‐1 blockade with Anakinra improves an experimental animal model of ARDS.